Analysis of Heat Potential in Solar Panels for Thermoelectric Generators using ANSYS Software - Catur Harsito; Teguh Triyono; Eki Rovianto (Civil Engineering Journal, 2022)
The growing demand for energy has an impact on the development of environmentally friendly renewable energy. The sun is energy that has the potential to be used as electrical energy through light energy and heat energy. Recently, research interest related to photovoltaic performance has increased. Several studies have investigated the effect of panel cooling on photovoltaic performance. In this study, the use of exergy solar panels is considered to improve performance by adding a thermoelectric system. Research work related to photovoltaic testing with thermoelectrics at low temperatures has not been carried out. Therefore, experimental methods to obtain temperature profiles and simulation methods to see the power potential generated from thermoelectrics have been carried out. The experimental method is carried out using mono-crystalline panels with type K sensors to retrieve temperature data and data acquisition as deviations from the current, voltage, and temperature results of the panel. The simulation model was carried out using the ANSYS software. Tests are carried out, taking into account the effect of back panel temperature on system performance. The results showed that the photovoltaic temperature fluctuated due to the influence of cloud cover, the highest photovoltaic temperature was 57°C, and the lowest temperature was 30°C. The maximum power produced by photovoltaic is 39.8W. It is then applied to the thermoelectric simulation based on the highest temperature, and the maximum power value is 1673.4 mW. This photovoltaic-thermoelectric generator system produces a 4.2% increase in power value over conventional photovoltaic systems. The findings in this study can be used as a reference for all types of low-temperature photovoltaic-thermoelectric systems. Doi: 10.28991/CEJ-2022-08-07-02 Full Text: PDF